Modulation of antibiotic resistance in Pseudomonas aeruginosa by ZnO nanoparticles - Bayroodi, Elnaz (Iran J Microbiol, 2016)
BACKGROUND AND OBJECTIVES: Bacterial resistance to conventional antibiotics has become a widespread public health problem. The aim of this study was to investigate the influence of zinc oxide nanoparticles (ZnO NPs) on the antibacterial activity of several conventional antibiotics against Pseudomonas aeruginosa. MATERIALS AND METHODS: ZnO NPs were prepared by solvothermal method and dispersed in glycerol with the help of ammonium citrate as a dispersant. The antibacterial effects of the resulting ZnO nanofluid, ceftazidime, tobramycin, and ciprofloxacin were investigated against two P. aeruginosa strains, including one clinical isolate and P. aeruginosa ATCC 9027 using microdilution method. For the evaluation of the combined effect of ZnO nanofluid and antibiotics, the fractional inhibitory concentration indices were calculated and isobolograms were plotted. RESULTS: Clinical strain in comparison to standard strain of P. aeruginosa showed more resistance to ZnO nanofluid and the antibiotics. ZnO nanofluid acted synergistically with ceftazidime and tobramycin against both strains. Combination of ZnO nanofluid and ciprofloxacin displayed synergistic and partial synergistic activity against clinical and standard strains of P. aeruginosa, respectively. CONCLUSION: The results suggest that bacterial resistance to antimicrobials could be reduced by the synergistic action of ZnO NPs.